The effect of employment on psychological health in mid-adulthood: findings from the 1970 British Cohort Study. Issue 5 (15th April 2008) - Cable, N; Sacker, A; Bartley, M
Abstract : Background: A negative link between unemployment and psychological health is well documented, yet little is known about the protective effect of continuous employment on psychological health. Method: In this prospective population-based cohort study, the effect of continuous employment on psychological health was examined, using individuals born in Great Britain during a week of April 1970. Respondents (2901 men and 3288 women) who were employed at the age of 26 years, with a complete employment history between ages 26 and 30 years and having information about cohabitation, social class and psychological and physical health at age 30 years, were included in the analysis. Results: Findings showed that continuous employment was associated with better psychological health in men. This effect was somewhat greater in those who showed evidence of poorer psychological health at the age of 26 years. In working women, cohabitation provided a protective effect on psychological health. Conclusion: The findings show that, for men, staying in continuous employment despite experiencing poor psychological health may contribute to better psychological health.